Primary Concurrent Chemoradiation in Head and Neck Cancers with Weekly Cisplatin Chemotherapy: Analysis of Compliance, Toxicity and Survival - Iqbal, Muhammad Shahid; Chaw, Cheng; Kovarik, Josef; Aslam, Shahzeena; Jackson, Aaron; Kelly, John; Dobrowsky, Werner; Kelly, Charles (International Archives of Otorhinolaryngology, 2017)
Introduction Concurrent chemoradiation is the standard of care in inoperable locally advanced squamous cell head and neck cancers. The most widely accepted schedule of concomitant cisplatin is 100mg/m2 given on a 3 weekly basis but the optimal regime is unknown.Objective The objective of this study is to assess the tolerability, compliance, and clinical outcomes of weekly cisplatin (40mg/m2).Methods During the period of January 2007–December 2009, we analyzed retrospectively 122 patients with histologically proven squamous cell carcinoma of head and neck (nasopharynx, oropharynx, larynx, hypopharynx, and oral cavity) treated with definitive chemoradiation. All patients received 63 Gy in 30 daily fractions with concomitant weekly cisplatin 40mg/m2. We assessed treatment toxicities and patient compliance. We estimated overall survival using the Kaplan-Meier method.Results Sixty-eight percent of patients managed to complete all six cycles of chemotherapy while 87% of patients completed at least 5 cycles of weekly cisplatin. Incidence of grade 3/4 toxicity was as follows: mucositis 33%, dermatitis 41%, dysphagia 15%, mouth/neck pain 17%, neutropenia 2%, and renal impairment 3%. 53% patients required at least one hospital admission for symptom control. The 5-year overall survival rate was 60%.Conclusion Concurrent chemoradiotherapy using weekly cisplatin at 40mg/m2 per week is an effective, well tolerated regimen allowing most patients to receive at least 5 cycles of chemotherapy. However, a phase III randomized control trial comparing the standard dose of 100mg/m2 cisplatin tri-weekly with a weekly regimen is needed to establish the long term clinical outcome.
Keywords: head and neck neoplasms; chemoradiotherapy; cisplatin